Birds’ community and the damage they generate in agricultural production in Alajuela, Costa Rica - Sánchez Núñez, Carol (2022)
Introduction. Knowledge of agroecosystems’avifauna allows to have a vision of its function in such production systems. Objective. To characterize the community of birds that uses the farming areas of Fabio Baudrit Moreno Agricultural Experimental Station and to describe the damage they produced to the crops on the site. Materials and methods. We carried out biweekly samplings using observation points. In each point we annotated richness, number of individuals per species, activity they performed, and if they were causing any damage. Results. We registered 967 individuals belonging to 55 species of birds. The species Volatina jacarina and Crotophaga sulcirostris were the most abundant with 18.8% and 10.2%, respectively, of the individuals recorded. Other species were Dives dives (9.8%), Zenaida asiatica (7.9%), Turdus grayi (6.1%) Columbina inca (6%) and Patagioenas flavirostris (5.9%). Twelve species (22%) caused some damage to the production. Damage was recorded in beans, tomatoes, papaya, corn, mangoes, cucumbers, and melon. Damage was also observed in the irrigation system caused by Quiscalus mexicanus. Mango was the crop birds visited the most with 29 species observed followed by acerola, beans, and corn crops with the presence of 20,18, and 16 species respectively. Conclusion. The site recorded 6% of the country’s avifauna suggesting that it offers conditions for the establishment of species that adapt to its ecosystems. 22% of the recorded bird species caused some kind of damage. Most of the individuals generating damage were recorded in beans (48 individuals), tomato (22), and corn (18).